Effect of the initiator on thermosensitive rate of poly(N-isopropylacrylamide) hydrogels (eXPRESS Polymer Letters)
As the main of thermosensitive polymeric materials, poly(N-isopropylacrylamide) (PNIPAM) undergoes volume changes in response to external temperature changes. While in some potential applications, a fast response rate is needed. In this article, effect of the initiator on thermosensitivity of PNIPAM hydrogels was carried out. The characterization of the resulting hydrogels was gravimetrically measured, and the result displays that with increasing the initiator dosage, much faster deswelling rate and much faster shrinking/swelling dynamic response are obtained.